2007
DOI: 10.1037/1076-898x.13.3.158
|View full text |Cite
|
Sign up to set email alerts
|

Expertise-based differences in search and option-generation strategies.

Abstract: The current work builds on option-generation research using experts of various skill levels in a realistic task. We extend previous findings that relate an athlete's performance strategy to generated options and subsequent choices in handball. In a 2-year longitudinal study, we present eye-tracking data to independently verify decision strategies previously inferred from patterns of generated options. A verbal protocol identified the option-generation process for each individual prior to an allocation decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
211
4
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(239 citation statements)
references
References 36 publications
19
211
4
5
Order By: Relevance
“…A second line of research has been motivated by expert decision-making, such as in chess or sport situations (Klein, Wolf, Militello, & Zsambok, 1995;Raab & Johnson, 2007). However, only very few studies have used ill-structured everyday scenarios to study option generation (e.g., Hausser, Schlemmer, Kaiser, Kalis, & Mojzisch, 2014;Kaiser et al, 2013).…”
Section: Apathy In Schizophrenia As a Deficit In The Generation Of Opmentioning
confidence: 99%
“…A second line of research has been motivated by expert decision-making, such as in chess or sport situations (Klein, Wolf, Militello, & Zsambok, 1995;Raab & Johnson, 2007). However, only very few studies have used ill-structured everyday scenarios to study option generation (e.g., Hausser, Schlemmer, Kaiser, Kalis, & Mojzisch, 2014;Kaiser et al, 2013).…”
Section: Apathy In Schizophrenia As a Deficit In The Generation Of Opmentioning
confidence: 99%
“…Furthermore, the total number of response options generated was negatively related to final decision quality. These results were extended by Raab and Johnson (2007) when comparing the performance of 69 expert, near-expert, and non-expert handball players. Using the same optiongeneration procedure, higher-skilled handball players generated fewer options and selected final options that were of higher quality than did the less-skilled players.…”
Section: Option-generation During Interventionmentioning
confidence: 99%
“…They found a significant effect of time on quality of move, such that those moves deliberated for longer were better than those generated first (cf. Johnson & Raab, 2007). Furthermore, both skill groups benefitted from taking extra time to deliberate over a move (cf.…”
Section: Option-generation During Assessmentmentioning
confidence: 99%
“…In a meta-analysis of 42 56 studies, Mann et al (2007) quantified the effect of experts having better decision-making 57 skills (e.g., picking up perceptual cues, visual search behaviours) compared to their lesser 58 skilled counterparts due to general training effects as a point-biserial correlation coefficient 59 (r pb ) of .31. Further, with a group of experts of various skill levels in handball, Raab and 60 Johnson (2007) provided longitudinal evidence that the first-option quality and choice time 61 of experts were better than those of their lesser skilled counterparts due to training effects. 62 The authors also showed that the visual search behaviour and therefore the acquisition of …”
mentioning
confidence: 99%